Micronutrient deficiency reshapes plant-microbe interaction networks: unraveling microbial community dynamics and functional adaptability in a sterile system - Jie Wu; Sauban Musa Jibril; Rong Liu; Bingjuan Yang; Yuru Xu; Ling Wang; Yi Wang; Chengyun Li (BMC Plant Biology)
Abstract Micronutrient deficiencies critically influence plant development and plant–microbe interactions, yet their role in reshaping microbial community dynamics remains poorly resolved. Here, we hypothesized that micronutrient deprivation alters plant-associated microbiomes through physiological and microbiota-mediated pathways, with cascading effects on plant growth and stress adaptation. Using axenic conditions, we subjected Gypsophila paniculata tissue culture seedlings to copper (Cu), manganese (Mn), molybdenum (Mo), and boron (B) deficiencies. We integrated 16S rRNA/ITS sequencing, functional prediction, and co-occurrence network analysis to unravel microbial responses. Our results demonstrate that Cu deficiency reduced bacterial alpha diversity (25% decline in Shannon index, p < 0.05), while Mn, Mo, and B deficiencies enhanced microbial richness (Chao1 increase: 15–30%). Taxonomic profiling revealed stress-adapted genera (Luteibacter, Lactobacillus, Akkermansia) as key responders, with Pseudomonas abundance decreasing under Cu/B deficiency but increases under Mn/Mo deprivation. Functional shifts included suppressed photosynthesis-associated bacteria under Cu limitation and enriched nitrogen-cycling taxa (e.g., denitrifiers) in Mo-deficient seedlings. Network analysis revealed intensified microbial interactions under Mn/Mo deficiency, with lower microbial interactions under Cu/B deficient treatments. Crucially, we propose a bidirectional "plant–microbe" regulatory axis: Cu deficiency directly impairs plant growth by disrupting photosynthetic symbionts and enriching potential pathogens, while Mn/Mo deprivation enriched endophytic taxa linked to potential nutrient metabolism and stress resilience. This study pioneers a sterile-system approach to decouple micronutrient effects from soil confounders, offering mechanistic insights into microbiome-driven plant adaptation.